Kolaborasi Edukasi Gizi dan Kesehatan Gigi Untuk Pencegahan Stunting di Desa Menur - Sa’adah, Naili; Nafa Aqila, Elmash; Aprilia, Sella Dwi; Rahayu, Putri; Antika, Dinda Rahma; Nugroho, Ilham Tegar Wahyu; Pratama, Arga Satya; Hadi Prasojo, Muhammad Naufal (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Menur Village is one of the villages dominated by rice fields and residential areas, so that most of its people work as farmers. In addition, there are also residents who work as factory workers or entrepreneurs to meet their daily needs. These geographical and socio-economic conditions cause the majority of the population of Menur Village to be in the lower middle economic level. The impact is that the level of education and literacy in the community, especially related to nutrition and dental health, is still very minimum. Objective: to increase public knowledge and understanding, especially pregnant women, breastfeeding mothers, and families with toddlers, regarding the relationship between balanced nutritional intake and dental health behavior in efforts to prevent stunting in children. Method: The method used in this community service activity is Participatory Action Research (PAR), where the Menur Village community is actively involved in every stage of the activity. Result: This activity succeeded in increasing participants' knowledge about the importance of balanced nutrition and dental health in preventing stunting, although there are still challenges in implementing a balanced diet due to economic limitations and low literacy. Conclusion: The active participation of participants, enthusiasm in discussions, and the involvement of Posyandu cadres showed that the educational and collaborative approach was able to strengthen community understanding and awareness of stunting prevention, so that it is expected to contribute to improving the quality of life and health of children in Menur Village.